Effect of of Levamisole as immunostimulatoron the humoral and cellular immune response in sheep vaccinated with Brucella melitensis Rev-1 vaccine: Yousif, A, A ; Talal A.K andAl- saigh,M,N - A., Yousif, A, (The Iraqi Journal of Veterinary Medicine, 2008)
This study was designed to determined the influence of levamisoleadministration as immunostimulator for sheep vaccinated with Brucellamelitensis vaccine (Rev-1). The sixty sheep (males and females) weredivided equally into four groups *The first group (vaccinated group ) theanimals were vaccinated with Rev-1 vaccine at a dose of 1 ml s/c whichcontain 2 x 109 viable bacteria *The second group ( vaccine andlevamisole ), was vaccinated with Rev-1 as the same of the first group aswell as levamisole was given orally at a dose of 10 mg / kg B.W a weekbefore vaccination and with vaccination and a week after vaccination andthen levamisole was given at monthly intervals up to the end of theexperiment.* Third group (levamisole group) was given levamisole orallyat a dose of 10 mg / kg B.W at the same regimen of the time of thesecond group.*The fourth group kept as a control group which was given 1 ml of PBSs/cThe humeral and cellular immunity assessed on animals at 0 time,2,4,6,8,10,12,14 weeks.The vaccinated animals showed a hightemperature after vaccination in the Ist and 2nd groups, the highest ratevalue was recorded in the first group 40.93C. Same trends were noticed inrespiratory and pulse rates. No changes were recorded in the third andfourth groups.The vaccine stimulate humeral immunity ( first and second groups ).Rose Bengal Test gave a positive result in both vaccinated groups only.The second group revealed high means significant antibody titer 1160.53than the first group, while the third and fourth groups showed a negativeresult in the antibody titer as detected by passive haemagglutination test(PHA).While the cellular immunity showed the following results .Delayed typehypersensitivity test was positive in the vaccinated groups and the secondgroupshowed significantly higher average in redness area and itsthickness, than the first group,while in third and fourth groups the resultswere negative .